2021
DOI: 10.3390/ani11020330
|View full text |Cite
|
Sign up to set email alerts
|

“I Couldn’t Have Asked for a Better Quarantine Partner!”: Experiences with Companion Dogs during Covid-19

Abstract: The Covid-19 pandemic has been found to negatively impact the psychological well-being of significant numbers of people globally. Many individuals have been challenged by social distancing mandates and the resultant social isolation. Humans, in our modern world, have rarely been as isolated and socially restricted. Social connectedness and support are critical protective factors for human survival and well-being. Social isolation can lead to loneliness, boredom, and can become a risk factor for physical and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
93
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(101 citation statements)
references
References 43 publications
7
93
0
1
Order By: Relevance
“…It is interesting to note that, although not statistically significant, more facilitators and participants indicated loving the experience when participants' dogs were present during the session compared to sessions in which participants held a pillow or blanket. This finding is consistent with recent human-animal research that has illuminated the comfort and companionship that pets can provide during the COVID-19 pandemic (Bussolari et al, 2021;Holland et al, 2021). These positive effects are perhaps due to pets' nonjudgmental acceptance and affection (Garrity et al, 1989;Zasloff and Kidd, 1994;Labrecque and Walsh, 2011), and their ability to reduce mental distress and improve their owners' quality of life (Aydin et al, 2012;Peacock et al, 2012;Hayden-Evans et al, 2018).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…It is interesting to note that, although not statistically significant, more facilitators and participants indicated loving the experience when participants' dogs were present during the session compared to sessions in which participants held a pillow or blanket. This finding is consistent with recent human-animal research that has illuminated the comfort and companionship that pets can provide during the COVID-19 pandemic (Bussolari et al, 2021;Holland et al, 2021). These positive effects are perhaps due to pets' nonjudgmental acceptance and affection (Garrity et al, 1989;Zasloff and Kidd, 1994;Labrecque and Walsh, 2011), and their ability to reduce mental distress and improve their owners' quality of life (Aydin et al, 2012;Peacock et al, 2012;Hayden-Evans et al, 2018).…”
Section: Discussionsupporting
confidence: 87%
“…Additionally, because of the growing body of the literature noting the positive impact of companion dogs for owners during the COVID-19 pandemic (Carr et al, 2020a;Bussolari et al, 2021;Hoffman, 2021;Johnson and Volsche, 2021), as well as the psychological benefits of dogs (Carr et al, 2020a,b;Gee et al, 2021), this study explored the impact of including participants' dogs in the body scan mindfulness exercise. The combined research suggesting that mindfulness training as well as companion dogs may both offer positive effects suggest that when combined, may offer a unique option for virtual mindfulness as a tool to reduce stress.…”
Section: Mindfulness Programsmentioning
confidence: 99%
“…Acquiring a dog has been associated with reduced loneliness [12,13], and there is some initial evidence that adolescents who own pets are less lonely than non-pet owners [14]. When access to face-to-face human social support is restricted due to the pandemic, pet owners may rely on their pets to supplement these interactions [4] and to diminish social isolation [15]. However, these findings are complex; for example, Powell et al [13] found that adjusting for covariates such as education level nullified the effects of dog acquisition on loneliness.…”
Section: Introductionmentioning
confidence: 99%
“…However, these findings are complex; for example, Powell et al [13] found that adjusting for covariates such as education level nullified the effects of dog acquisition on loneliness. In addition, the majority of existing research to date on pets during the pandemic has focused on adults [1,[15][16][17], with a range of mixed findings across samples and outcomes. To complement these initial studies, there is still a need for complementary research assessing similar relationships in youth.…”
Section: Introductionmentioning
confidence: 99%
“…As noted by Wiltzius et al suggesting that people with limited means should not have pets is an "untenable solution" (21). Additionally, with research suggesting that pets play a critical role in mitigating COVID-19 related stress (29)(30)(31), and numerous antidotal reports that pet adoptions have dramatically increased since the pandemic began, it is more critical than ever to support these vulnerable pet owners. Assisting these families that struggle with financial constraints that prevent them from accessing veterinary care could help them keep their pets at home (20).…”
Section: Discussionmentioning
confidence: 99%